Derechos de los afrodescendientes desde la perspectiva del Sistema Interamericano de Derechos Humanos, análisis caso: Colombia - Rozo Barrera, Esther Paola (Derecho, Ciencias Jurídicas y Políticas, 2018)
This article explains the perspective of the inter-American system in relation to the human rights of Afro-descendants in Latin America as a vulnerable group, the field of interest is centered on the integral legal framework created by the international community. Based on the analysis of the main legal publications of the system, by the case study that the inter-American court has known and by a tour of the legislation is Colombia; concludes that they have been victims of racial discrimination, racism, xenophobia and all related forms of intolerance reflecting a series of barriers in the situation they face in the Americas.